Diversity of Pelagic and Benthic Bacterial Assemblages in the Western Pacific Ocean - Wang, Mengmeng; Ma, Yiyuan; Feng, Chunhui; Cai, Lei; Li, Wei (Frontiers in Microbiology, 2020)
Despite numerous studies of marine prokaryotes, the vertical distribution patterns of bacterial community, either on the taxonomic composition or the functional structure remains relatively unexplored. Using HiSeq-derived 16S rRNA data, the depth-related distribution patterns of taxonomic diversity and functional structure predicted from diversity data in the water column and sediments of the Western Pacific Ocean were explored. The OTU richness declined along the water column after peaking between 100 to 200 m deep. Relative abundance of Cyanobacteria and SAR11 decreased significantly with depth, while Actinobacteria and Gammaproteobacteria increased. This clearly mirrors the vertical distribution pattern of predicted functional composition with the shift between phototrophic to chemoheterotrophic groups from the surface to the deeper layers. In terms of community composition and functional structure, the epipelagic zone differed from other deeper ones (i.e. meso-, bathy- and abyssopelagic zones) where no obvious differences were detected. For the epipelagic zone, temperature, dissolved oxygen and salinity were recognized as the crucial factors shaping both community composition and functional structure of bacteria. Compared with water samples, benthic sediment samples harbored unexpectedly higher read abundance of Proteobacteria, presenting distinguishable taxonomic and functional compositions. This study provides novel knowledge on the vertical distribution of bacterial taxonomic and functional compositions in the western Pacific.